Adrenal Incidentalomas: Should We Operate on Small Tumors in the Era of Laparoscopy? - Michał Pędziwiatr; Michał Natkaniec; Mikhail Kisialeuski; Piotr Major; Maciej Matłok; Damian Kołodziej; Anna Zub-Pokrowiecka; Piotr Budzyński; Andrzej Budzyński (International Journal of Endocrinology)
Tumor size smaller than 4 cm as an indication for surgical treatment of incidentaloma is still a subject of discussion. Our aim was the estimation of the incidence of malignancy and analysis of treatment outcomes in patients with incidentaloma smaller than 4 cm in comparison to bigger lesions. 132 patients who underwent laparoscopic adrenalectomy for nonsecreting tumors were divided into two groups: group 1 (55 pts., size < = 40 mm) and group 2 (77 pts., size > 40 mm). Operation parameters and histopathological results were analyzed. No differences in group characteristics, mean operation time, and estimated blood loss were noted. Complications in groups 1 and 2 occurred in 3.6% and 5.2% of patients, respectively (P=0.67). Malignancy in groups 1 and 2 was present in 1 and 6 patients, respectively (P=0.13). Potentially malignant lesions were identified in 4 patients in group 1 and 4 patients in group 2 (P=0.39). The results do not allow for straightforward recommendations for surgical treatment of smaller adrenal tumors. The safety of laparoscopy and minimal, but impossible to omit, risk of malignancy support decisions for surgery. On the other hand, the risk of malignancy in smaller adrenal tumors is lower than surgical complications, which provides an important argument against surgery.